The hypotensive effect of activated apelin receptor is correlated with β-arrestin recruitment. (May 2018) - Besserer-Offroy, Élie; Bérubé, Patrick; Côté, Jérôme; Murza, Alexandre; Longpré, Jean-Michel; Dumaine, Robert; Lesur, Olivier; Auger-Messier, Mannix; Leduc, Richard; Marsault, Éric; Sarret, Philippe
Graphical abstract: Abstract: The apelinergic system is an important player in the regulation of both vascular tone and cardiovascular function, making this physiological system an attractive target for drug development for hypertension, heart failure and ischemic heart disease. Indeed, apelin exerts a positive inotropic effect in humans whilst reducing peripheral vascular resistance. In this study, we investigated the signaling pathways through which apelin exerts its hypotensive action. We synthesized a series of apelin-13 analogs whereby the C-terminal Phe 13 residue was replaced by natural or unnatural amino acids. In HEK293 cells expressing APJ, we evaluated the relative efficacy of these compounds to activate Gαi1 and GαoA G-proteins, recruit β-arrestins 1 and 2 (βarrs), and inhibit cAMP production. Calculating the transduction ratio for each pathway allowed us to identify several analogs with distinct signaling profiles. Furthermore, we found that these analogs delivered i.v. to Sprague-Dawley rats exerted a wide range of hypotensive responses. Indeed, two compounds lost their ability to lower blood pressure, while other analogs significantly reduced blood pressure as apelin-13. Interestingly, analogs that did not lower blood pressure were less effective at recruiting βarrs. Finally, using Spearman correlations, we established that the hypotensive response was significantly correlated with βarr recruitment but not with G protein-dependent signaling. In conclusion, our results demonstrated that the βarr recruitment potency is involved in the hypotensive efficacy of activated APJ.